ANALYSIS OF BANK HEALTH AT INDONESIA STATE-OWNED BANK USING RGEC METHOD AT BRI, BNI, AND BANK MANDIRI FOR PERIODS 2011-2015 - -, Azeharie; Marcellina, Willis; -, Wahjono; Imam, Sentot (Prosiding International conference on Information Technology and Business (ICITB), 2017)
The objective of this study is to analyze the financial performance of three state-owned banks in Indonesia (BNI, BRI, and Bank Mandiri) for the period of 2011-2015 by using the approach of RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) method. The analysis tool which is used is the RGEC Method. This study uses descriptive method with quantitative approach. Population for this study are three state-owned banks in Indonesia that already published their financial statement for the period of year 2011 until 2015. The data collecting method used is the documentation method and literature method. Result of the study shows the overall financial performance of these three state-owned banks for the period of 2011-2015 on Risk Profile aspect which is done by analyzing the Credit Risk which is represented by NPL ratio is assessed as healthy, while from the analysis of Liquidity Risk yang which is represented by LDR ratio is also assessed as healthy. Furthermore from the aspect of Good Corporate Governance (GCG), banks performance is rated as very healthy. Overall financial performance from Earning aspect which is calculated by analyzing the NIM and ROA ratio is also assessed as healthy. Finally, the overall financial performance from Capital aspect which is calculated by analyzing the comparison between the capital ratio towards the Risk Weighted Asset (RWA) which is represented by the CAR ratio is assessed as healthy.Keywords : Bank Health, RGEC Method, BRI, BNI, Bank Mandiri